Real-time imaging of the dynamics of secretory granules in growth cones - Abney, JR (1999)
Secretory granules containing a hybrid protein consisting of the regulated secretory protein tissue plasminogen activator and an enhanced form of green fluorescent protein were tracked at high spatial resolution in growth cones of differentiated PC12 cells. Tracking shows that granules, unlike synaptic vesicles, generally are mobile in growth cones. Quantitative analysis of trajectories generated by granules revealed two dominant modes of motion: diffusive and directed. Diffusive motion was observed primarily in central and peripheral parts of growth cones, where most granules diffused two to four orders of magnitude more slowly than comparably sized spheres in dilute solution. Directed motion was observed primarily in proximal parts of growth cones, where a subset of granules underwent rapid, directed motion at average speeds comparable to those observed for granules in neurites. This high-resolution view of the dynamics of secretory granules in growth cones provides insight into granule organization and release at nerve terminals. In particular, the mobility of granules suggests that granules, unlike synaptic vesicles, are not tethered stably to cytoskeletal structures in nerve terminals. Moreover, the slow diffusive nature of this mobility suggests that secretory responses involving centrally distributed granules in growth cones will occur slowly, on a time scale of minutes or longer.